Digital ESG monitoring in SMEs: Enhancing traceability and compliance through technology - Shahzad, Rabi; Maity, Richik; Hammad, Muhammad Yahya; Qamar, Shujahat (Akademia Baru, 2025)
In the period of sustainable development, Environmental, Social, and Governance (ESG) reporting has turned a critical practice for enterprises. However, Small and Medium Enterprises (SMEs) look unique challenges in ESG compliance, particularly in tracking and transparency. This paper explores how digital technologies such as blockchain, Internet of Things (IoT), cloud computing, and AI enable ESG traceability and monitoring within SMEs. Throughout a structured review of recent 50 literature, the study investigates how digital ESG systems support regulatory compliance, stakeholder engagement, and sustainable development. We propose a framework for implementing digital ESG monitoring in SMEs and highlight practical challenges and opportunities. This review offers insights into scalable strategies and digital toolkits that SMEs can adopt to meet growing regulatory and societal expectations.